The Hidden Cost of Globalization: Import Competition and Mental Distress - Italo Colantone; Rosario Crinò; Laura Ogliari (Center for Economic Studies and ifo Institute (CESifo), 2015)
We study the effect of import competition on workers' mental distress. To this purpose, we source information on the mental health of British workers from the British Household Panel Survey, and combine it with measures of import competition in more than 100 industries over 2001-2007. We find an increase in import competition to have a positive, statistically significant, and large impact on mental distress. The effect is strikingly robust to controlling for a wide range of individual, household, and industry characteristics. We show that part of the effect is due to import competition worsening the current labor market situation of individuals, in terms of higher probability of job displacement and lower wage growth. Additionally, and most importantly, we show that import competition worsens mental health also for individuals witnessing no change in observable labor market conditions, by increasing stress on the job and worsening expectations about the future.
Keywords: F10; 330; subjective well-being; trade adjustment costs; individual-level panel data